Desconstrução dos estereótipos de gênero na primeira infância: uma abordagem guiada pelo design estratégico - Comparin, Jaqueline Freitas (Universidade do Vale do Rio dos Sinos, 2023)
In the society we live in today, we talk a lot about gender relations, in the most different spaces and from different points of view. This variety of spectrums, affects discussions especially when we talk about the young child, the stereotypes associated with gender and, above all, the practices adopted in educational institutions. Faced with a social problem that is so complex, we need to find paths that lead to social innovations guided by strategic dialogues. The objective of this research is to propose a projectual approach, based on strategic design, to stimulate the deconstruction of gender stereotypes since early childhood. In this way, and in light of these principles, we developed a qualitative, social research by the lens of Strategic Design. We held two rounds of workshops, one with children and one with designers specialized in education. As a result, we propose principles that can unfold into practices capable of fostering new worldviews, and strategic dialogues about gender in teaching-learning environments.
Keywords: Design estratégico; Educação; Gênero; Infância; Strategic design; Education; Gender; Childhood; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial